Clinical and nerve conduction features in Guillain−Barré syndrome associated with Zika virus infection in Cúcuta, Colombia. (6th February 2018) - Uncini, A.; González‐Bravo, D. C.; Acosta‐Ampudia, Y. Y.; Ojeda, E. C.; Rodríguez, Y.; Monsalve, D. M.; Ramírez‐Santana, C.; Vega, D. A.; Paipilla, D.; Torres, L.; Molano‐González, N.; Osorio, J. E.; et al.
Abstract : Background and purpose: Zika virus (ZIKV) infection has been associated with an increased incidence of Guillain−Barré syndrome (GBS) but the relative frequency of acute inflammatory demyelinating polyradiculoneuropathy (AIDP) and axonal GBS subtypes is controversial. Methods: Twenty GBS patients diagnosed according to the Brighton criteria during the ZIKV outbreak in Cúcuta, Colombia, were evaluated clinically and electrophysiologically. The electrodiagnosis of GBS subtypes was made according to a recently described criteria set that demonstrated a high diagnostic accuracy on the basis of a single test. The electrophysiological features of 34 Italian AIDP patients were used as control. Results: All patients had symptoms compatible with ZIKV infection before the onset of GBS and ZIKV infection was laboratory confirmed through a plaque reduction neutralization test (PRNT90 ) in 100% of patients. The median time from onset of ZIKV infection symptoms to GBS was 5 days (interquartile range 1–6 days). Cranial nerve palsy was present in 85% of patients (facial palsy in 75%, bulbar nerve involvement in 60%), autonomic dysfunction in 85%, and 50% of patients required invasive mechanical ventilation. AIDP was diagnosed in 70% of patients. 40% of nerves of AIDP patients showed a prevalent distal demyelinating involvement but this pattern was not different from the Italian AIDP patients without ZIKV infection. Conclusions: Guillain−Barré syndrome associated with ZIKV infection in Cúcuta is characterized by a high frequency of cranial nerve involvement, autonomic dysfunction and requirement of mechanical ventilation indicating an aggressive and severe course. AIDP is the most frequent electrophysiological subtype. Demyelination is prevalent distally but this pattern is not specific for ZIKV infection.